Peningkatan 'Sense of Business' Dalam Kemampuan Wirausaha Mahasiswa - Setiawan, Agus; Mardiana, Tria; Ari Purnomo, Tuessi; Raliby Al Manan, Oesman (Jurnal Surya Masyarakat, 2020)
The purpose of this program is to optimize the interests and abilities of entrepreneurs owned by students. The subjects used in this program are students who already have an entrepreneurial program. The method is carried out through fostering sustainable entrepreneurs, by applying a questionnaire as the main instrument in the acquisition of data sources from the implementation ofthe program. The results obtained in the implementation of the program, to optimize entrepreneurial interest increased by 65%, while the optimization of student entrepreneurship in terms of entrepreneurial basic knowledge increased by 73%.